Financial Performance Analysis on KALBE FARMA Tbk as Compared to other national and International Pharmaceutical Companies - Ivan, Vincentius; Noveria, Ana (Journal of Business and Management, 2014)
Indonesia is a very big nation. It consists of 13,466 islands, and currently being the 4th highest populated country in the world with a population number of over 238 million people. Even until today, the human race still cannot live disease-free. We still got diseases because viruses are also evolving, like us. This has created an opportunity for pharmaceutical industry to make profit from selling drugs and medicines. There are many pharmaceutical companies in Indonesia, consisting of national and multi-national companies. Kalbe Farma, which was created in 1966, is the one with the biggest market share in the Indonesian pharmaceutical industry currently.The formulation of the problem in this research is about how good is the Kalbe Farma’s financial performance, analyzed using financial ratios of the company which calculated based on their annual report, DuPont formula, and Compound Annual Groth Rate (CAGR), then compared to other companies from the similar industry, nationally and internationally.The research is aimed at finding out the performance of Kalbe Farma Pharmaceutical Company financially, and then to compare the result with other companies which are Tempo Scan, Kimia Farma, Merck Indonesia, Darya Varia (national) and Pfizer (international).Keywords: Pharmaceutical industry, financial ratios, DuPont formula, CAGR, financial performance.